State of the art of all-Vanadium Redox Flow Battery: A Research Opportunities - Mohd Rusllim, Mohamed; Hamzah, Ahmad; Mazrul Nizam, Abu Seman (2012)
This paper deals with the state of the art of redox flow battery (RFB) focusing on vanadium-based electrolytes. A broad review on energy storage technologies is first presented to bring RFBs system into perspective subsequently, discussions are focusing on vanadium-based RFB in regards to justify the motivation factors of chosen V-RFB as a system to be studied.Research potential and challenges for V-RFB system are discussed in detail.